Sororidad en los procesos de envejecimiento femenino (2018)
Sorority encompasses the practices of collaboration and support in relations between women and is the propitious space for the construction of new ways to signify female old age. We present results of a qualitative study using focus groups, which aimed to describe and categorize the types of relational configurations that remain unchanged or change towards sorority in the female aging process. Findings describe the need to implement actions to reduce ageism, not only in terms of the experiences women go through, but also towards aging in general. One of the measures we can take is undoubtedly the construction of women circle sorority, which leads to collective empowerment of gender. The female body is a focus of attention in terms of what it lives and experiences, and the right to have love and sexuality throughout life is also highlighted. We then created an intervention proposal to work on the perception of the female body and its experience in the aging process. The proposed intervention is a workshop, based on the narrative model of Michael White and David Epston.